Lycopene Alleviates the Adverse Effects of Feeding High-Lipid Diets to Hybrid Grouper (♀Epinephelus fuscoguttatus ×♂E. lanceolatus) - Menglong Zhou; Hao Liu; Baiquan Lu; Biao Li; Weibin Huang; Beiping Tan; Yuanzhi Yang; Xiaohui Dong; Haitao Zhang (Aquaculture Nutrition, 2023)
It has been found that high-lipid diets (HLDs) disrupt lipid metabolism in fish, leading to an excessive accumulation of lipids in various tissues of the fish body. The objective of this study was to investigate if the inclusion of lycopene (LCP) in an HLD may mitigate the adverse consequences of excessive dietary lipid intake in hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus). The experimental design incorporated a control group (L0), which was administered a diet consisting of 42% protein and 16% lipid. The diets for groups L1, L2, and L3 were developed by augmenting the control diet with 100, 200, and 400 mg/kg LCP, respectively. The duration of the trial spanned a period of 42 days. The results of the study showed that the weight gain rate (WGR) and protein efficiency ratio (PER) of the three LCP treatment groups (L1, L2, and L3) tended to increase and then decrease, with a significant increase in WGR and PER in L2 (P <0.05). Visceral somatic index and hepatic somatic index tended to decrease and then increase in all treatment groups, with a significant decrease in L2 (P <0.05). In serum dietary LCP significantly reduced triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL) content and significantly increased high-density lipoprotein (HDL) content (P <0.05). In the liver, dietary LCP reduced TC, TG, and very LDL levels and improved lipoprotein lipase, hepatic lipase, fatty acid (FA) synthetase, and acetyl-CoA carboxylase activities. The number and area of hepatic lipid droplets decreased significantly with increasing LCP content. In the liver, the addition of appropriate levels of LCP significantly upregulated lipoprotein lipase (lpl) and peroxisome proliferator-activated receptor α (pparα). In summary, dietary LCP improves growth and reduces lipid deposition in the liver of hybrid grouper by increasing lipolytic metabolism and decreasing FA synthesis. Under the experimental conditions, the fitted curve analysis showed that the recommended LCP additions to the high lipid diet for juvenile hybrid grouper were 200–300 mg/kg.